Evaluation of different tricaine (MS-222) concentrations on the transport of juvenile Peruvian grunt (Anisotremus scapularis) - Rosado, Maryandrea (2017)
The use of tricaine (MS-222) as sedative agent for transporting of Anisotremus scapularis juveniles was evaluated. A simulated transport of 24 hours was performed at two temperatures (15 and 19 °C) using the anaesthetic concentrations of 0, 15, 20 and 25 mg.L-1 in polyethylene bags (50% seawater - 50% pure oxygen). At the beginning and the end of the simulation temperature, dissolved oxygen saturation, pH and ammonia excretion rate were monitored. On fishes, the loss of balance (%) and survival (%) were monitored at the end of the simulation and after an additional recovery time of 24 hours. The results showed that use of tricaine favours the reduction of ammonia excretion, however, tricaine doses over 20 mg.L-1 significantly increase the loss of balance in fish. Furthermore, the sedating effect is magnified at lower temperature (15 °C). On the other hand, the water pH is affected showing an average decrease of 1.44 during the transport simulation in all treatments. Based on the results, transport of Peruvian grunt juveniles using tricaine in a dose of at 15 mg.L-1 at 19 °C is recommended.